Detecting T cell receptors involved in immune responses from single repertoire snapshots - Pogorelyy, Mikhail V; Minervina, Anastasia A; Shugay, Mikhail; Chudakov, Dmitriy M; Lebedev, Yuri B; Mora, Thierry; Walczak, Aleksandra M (PLoS biology, 2019)
Hypervariable T cell receptors (TCRs) play a key role in adaptive immunity, recognizing a vast diversity of pathogen-derived antigens. Our ability to extract clinically relevant information from large high-throughput sequencing of TCR repertoires (RepSeq) data is limited, because little is known about TCR-disease associations. We present Antigen-specific Lymphocyte Identification by Clustering of Expanded sequences (ALICE), a statistical approach that identifies TCR sequences actively involved in current immune responses from a single RepSeq sample and apply it to repertoires of patients with a variety of disorders - patients with autoimmune disease (ankylosing spondylitis [AS]), under cancer immunotherapy, or subject to an acute infection (live yellow fever [YF] vaccine). We validate the method with independent assays. ALICE requires no longitudinal data collection nor large cohorts, and it is directly applicable to most RepSeq datasets. Its results facilitate the identification of TCR variants associated with diseases and conditions, which can be used for diagnostics and rational vaccine design.
Keywords: receptory antigenů T-buněk; vysoce účinné nukleotidové sekvenování; Complementarity Determining Regions; Adaptive Immunity; antigeny virové; Receptors, Antigen, T-Cell; shluková analýza; Cluster Analysis; hypervariabilní oblasti; Humans; antigeny; Sequence Analysis, DNA; imunoterapie; sekvenční analýza DNA; Immunotherapy; Antigens, Viral; lidé; High-Throughput Nucleotide Sequencing; adaptivní imunita; Antigens